Knowledge of the inhabitants of Lubelskie region on proper eating habits - Dorota Weber; Andrzej Stanisławek; Dorota Nalepa (Kazimierz Wielki University, 2017)
Introduction   Due to the fact that care about health, where proper eating habits are one of its constituents, exerts a strong impact on both social and economic life of a country, it is not just an individual case of each person, but a public matter.  The state of health status is obviously subject to a number of factors. However, the habits and customs with regard to daily habits are of particular importance due to the significance of food for the physical existence of each human body. These habits are formed in childhood and youth, however they undergo modifications throughout the whole life. Quite frequently the possessed knowledge is not a sufficient motivation to make great changes in the manner of eating, thus it does not change the eating habits. The aim of the paper is to determine the level of knowledge of clinic patients, selected at random, on proper eating habits. Materials and methods The research was conducted during the period of January-February 2016 year in a Lublin clinic. The investigation comprised 148 respondents. The method used in the research was a diagnostic survey, and the selected technique was a questionnaire conducted among the respondents, using a birth certificate, an interview and an anthropometric study. The study included 148 persons, who were further divided into two groups: students and workers. The respondents were the inhabitants of Lublin and nearby villages. The survey findings underwent a static programme analysis in Statistica 9.1 software (StatSoft, Poland). Conclusions The identification of nutritional knowledge and dietary behaviours of consumers as well as determination of the level and diversity of their nutritional awareness should become the basis for the preparation of guidelines on the content of broadcasts in order to promote healthy eating habits among consumers of different groups.